The international role of education in sustainable lifestyles and economic development - Xiangdan Piao; Shunsuke Managi (Scientific Reports, 2023)
Abstract Improved economic growth and environmental protection are necessary to achieve the United Nations’ Sustainable Development Goals. This study examines the relationship between people’s education levels and sustainable lifestyles in protecting the environment and economic growth, as expressed by the increase in household equivalent income. We conducted an original cross-sectional survey, which yielded 100,956 valid observations in 37 countries. The factors included educational level, sustainable lifestyle with natural resource consumption, and household equivalent income for economic development. We used logit and ordered logit model and applied an ordinary linear regression model after confirming the association between education and income. Our analyses found that higher educational levels were associated with an increase in specific environmentally friendly behaviors and sustainable energy consumption. Individuals in the higher educational level group tended to consume recycled goods, purchase energy-saving household products, conserve electricity, and separate their waste. Additionally, higher levels of education were positively associated with equivalent household income in all 37 countries, indicating better economic development. Thus, our study underscores the importance of improving education at the broad population level to promote economic development and establish cooperative human behaviors necessary to sustain the environment.